Dose–response study of prophylactic nitroglycerin for prevention of pituitrin-induced hypertension during laparoscopic myomectomy: a prospective, randomized study - Wang, Jin; Xu, Qiang; Xiao, Fei; Chen, Gang (Frontiers in Medicine, 2023)
Objective To determine the dose–response of nitroglycerin in preventing pituitrin-induced hypertension in patients undergoing laparoscopic myomectomy. Methods Hundred patients scheduled for elective laparoscopic myomectomy were randomly allocated into one of five groups (n = 20) to receive intravenous bolus of prophylactic nitroglycerin at 0, 50, 75, 100, and 125 μg one minute following administration of 3 IU of pituitrin into the myometrium. The patients were monitored for pituitrin-induced hypertension with the primary outcome to determine the effective dose of prophylactic nitroglycerin, defined as complete prevention of pituitrin-induced hypertension during the study period. Probit analysis was used to calculate the median effective dose (ED50) and 95% effective dose (ED95) of prophylactic nitroglycerin. Results Hypertension occurred in 19/20, 10/20, 8/20, 2/20, and 1/20 in patients who received 0, 50, 75, 100, and 125 ug of prophylactic nitroglycerin, respectively. The calculated ED50 and ED95 of nitroglycerin for preventing hypertension were 54 μg (95%CI: 35~66 μg) and 136 μg (95%CI: 105~289 μg). Conclusion A prophylactic bolus of nitroglycerin administered immediately following injection of pituitrin into the myometrium during laparoscopic myomectomy effectively prevented pituitrin-induced hypertension, with the ED50 and ED95 of 54 μg and 136 μg, respectively. This information would be useful for clinical practice. Clinical trial registration www.chictr.org.cn, Identifier ChiCTR2200062282.